2007
DOI: 10.3748/wjg.v13.i43.5718
|View full text |Cite
|
Sign up to set email alerts
|

Silencing SMYD3 in hepatoma demethylates RIZI promoter induces apoptosis and inhibits cell proliferation and migration

Abstract: AIM:To investigate the role of SMYD3 in hepatocellular carcinoma (HCC) development and progression and to verify whether its regulation activity was through RIZ1 inactivation. METHODS:Expression of SMYD3 in HCC cell lines and tissues were measured; silencing of SMYD3 by RNA interference (RNAi) was effectuated, hepatoma cell proliferation, migration and apoptosis were tested, with RIZ1 CpG promoter methylation, and corresponding mRNA expression were investigated. RESULTS: S M Y D 3o v e r -e x p r e s s i o n i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 25 publications
1
38
1
Order By: Relevance
“…Therefore, it is possible that the suppression of TE-specific genes, such as Cdx2 and Eomes, could account for a defect in the ability of Smyd3-knockdown embryos to attach to a matrix substrate in vitro. Furthermore, it has been reported that Smyd3 knockdown induces apoptosis in cancer (Chen et al 2007). In the present study, however, we showed that the number of apoptotic cells was not increased in Smyd3-knockdown embryos.…”
Section: Role Of Smyd3 In Embryonic Lineage Commitmentcontrasting
confidence: 87%
See 2 more Smart Citations
“…Therefore, it is possible that the suppression of TE-specific genes, such as Cdx2 and Eomes, could account for a defect in the ability of Smyd3-knockdown embryos to attach to a matrix substrate in vitro. Furthermore, it has been reported that Smyd3 knockdown induces apoptosis in cancer (Chen et al 2007). In the present study, however, we showed that the number of apoptotic cells was not increased in Smyd3-knockdown embryos.…”
Section: Role Of Smyd3 In Embryonic Lineage Commitmentcontrasting
confidence: 87%
“…Because it has been reported that Smyd3 knockdown induces apoptosis in human cancer cells (Chen et al 2007), we investigated the effects of Smyd3 knockdown on apoptosis in mouse peri-implantation embryos. However, there was no difference in the number of TUNEL-positive cells between Smyd3-knockdown and control embryos (Fig.…”
Section: Knockdown Of Smyd3 Does Not Induce Apoptosis During Peri-impmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal expression of RIZ1 is associated with the tumorigenesis of a variety of human tumors, including nasopharyngeal, breast, liver and cervical among other cancers (16,17). Nomoto et al (18) reported that the frequency of RIZ1 gene methylation was 45.2% among patients with HCC in Japan.…”
Section: Gstp1 Methylation P16 Methylation --------------------------mentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) research has shown that RNAi targeting genes are related to initiation, development and metastasis of HCC [2][3][4] . Signal transducer and activator of transcription 3 (STAT3) is an important member of the family of STAT.…”
Section: Introductionmentioning
confidence: 99%